If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4y-4+2(4y+1)=4(y+4)
We move all terms to the left:
4y-4+2(4y+1)-(4(y+4))=0
We multiply parentheses
4y+8y-(4(y+4))+2-4=0
We calculate terms in parentheses: -(4(y+4)), so:We add all the numbers together, and all the variables
4(y+4)
We multiply parentheses
4y+16
Back to the equation:
-(4y+16)
12y-(4y+16)-2=0
We get rid of parentheses
12y-4y-16-2=0
We add all the numbers together, and all the variables
8y-18=0
We move all terms containing y to the left, all other terms to the right
8y=18
y=18/8
y=2+1/4
| -2(7b+8)=8-8b | | -5x-7(-7-4x)=2(3x-4) | | 4(2x-6)=27 | | 4.6-4x=-22 | | g=4+0.93/3 | | 4(w+8)=7+4w | | -4(u-8)=-6u+22 | | 16.57=3g+3.64 | | 31-2(6x-50)=47 | | 6(x-7=10(x+4) | | 3(x-16)=56 | | b(b-3)=10 | | 2(4x)+2(3x+2)=116 | | 8x-(2x+8)=8x-20 | | 8x+11+14x-1=0 | | -2(8v-9)+2v=4(v+4) | | 18-4k=-10=4k | | 1/2(2x-20)=2(3x-5) | | 4(3x+7)−6(4x−7)=11x+3(4x−6) | | 12(x-2)+3x=1.2(x+6)+2 | | 11x-1=x+9 | | 55=55-11u | | 28a=-84 | | 3d-5=-2+3d | | -8y-13=14y+11 | | 7(v-1)-5=-6(-5v+4)-5v | | x+9=11x-1 | | 2x+3=3x−1 | | a/5-4=16 | | 12.12=2g+3.74 | | 9(11)+25+17y+15=180 | | -20=3/2w |